Konsep Ikhlas dalam Implementasi Daqu Method di Pesantren Tahfizh Darul Qur’an Bandung - Ramyani, Intan (Jurnal Riset Agama, 2022)
Ikhlas is one of the characteristics that every Muslim must have, sincerity is one of the peaks of godly enjoyment for a servant, because he only expects goodness from his God. Of course, having a sincere attitude cannot be formed suddenly, it requires a process of self-formation. Daqu Method is one of the methods in self-formation to achieve sincere attitude and all its implementation, therefore researchers have a basic purpose in this study with the basis of urgency to provide reference methods in undergoing the process of self-forging to be a better human being in the view of religion. Daqu method contains disciplines that contain consistent and continuous worship activities, these disciplines slowly include sincere values to everyone who undergoes the method. Daqu method proved successful in forging one's character in order to reach one of the peaks of godliness, to reach the purpose of the method, the people have to do a consitence diciplines.